Bone marrow immune cells and drug resistance in acute myeloid leukemia - Miao Zhang; Miao Zhang; You Yang; You Yang; Jing Liu; Jing Liu; Ling Guo; Ling Guo; Qulian Guo; Qulian Guo; Wenjun Liu; Wenjun Liu (Experimental Biology and Medicine)
In recent years, the relationship between the immunosuppressive niche of the bone marrow and therapy resistance in acute myeloid leukemia (AML) has become a research focus. The abnormal number and function of immunosuppressive cells, including regulatory T cells (Tregs) and myeloid-derived suppressor cells (MDSCs), along with the dysfunction and exhaustion of immunological effector cells, including cytotoxic T lymphocytes (CTLs), dendritic cells (DCs) and natural killer cells (NKs), can induce immune escape of leukemia cells and are closely linked to therapy resistance in leukemia. This article reviews the research progress on the relationship between immune cells in the marrow microenvironment and chemoresistance in AML, aiming to provide new ideas for the immunotherapy of AML.